Numerical simulation of the ice hockey slap shot - Kays, B.; Smith, L. (Procedia Engineering, 2015)
With the introduction of new materials in ice hockey sticks in the past several decades there is increasing interest in material properties that affect the slap shot. Stick interrogation is complicated due to the variation from player to player and even shot to shot. To isolate the parameters affecting puck speed, a finite element model was employed that simulated a slap shot. The stick was modeled as a linear elastic material and the puck was modeled as a viscoelastic material. Puck speeds found good agreement with experiment and increased slightly with increasing shaft stiffness. The trend was attributed to the constant displacement boundary condition used in the model, which may be more appropriate for low force wrist shots, however. Stick mass moment of inertia had no effect on puck speeds while impacting the puck closer to the toe resulted in higher shot speeds.